Propuesta metodológica para la gestión de residuos hospitalarios peligrosos - Caso de estudio departamento del Meta (2011)
The potential risk presented from inadequate handling of hazardous solid waste is a problem of public health, environmental planning, nosocomial and epidemiological illnesses (OMS Bulletin 8-2004).The general objective of this study was to get to know the current issues present in the selected samples of IPS’s, in regards to these hazardous hospital waste, to identify the reason and cause that prevents its proper management with the methodological proposal of the findings to contribute and minimize the environmental and social impact caused for these centers and to provide the simple tools to improve the internal processing of the hazardous waste; thus contributing to expand the quality management, integrating social and environmental aspects.This investigation is based on a non probabilistic sample from seven health service institutions( IPS) from public and private organizations, located in four (4) towns belonging to the state of Meta (Colombia) where 74% of the population of this state’s health care is provided.During the research, it was identified that a very well designed norm which encloses all national and international regulations exists, but in real life these laws and self-regulation are not carried out by those that generate hazardous waste and by the local authorities. These IPS do not register the amount and type of hazardous waste that are produced daily; for this reason there is no updated or precise information . Also, we noted that even though the human factor is imperative in the success of proper management of hazardous hospital waste, the IPS’s have not developed formative and educational programs to strengthen these norms and regulation for enforcement of current national and international laws.